2012
DOI: 10.1371/journal.pone.0029962
|View full text |Cite
|
Sign up to set email alerts
|

Basin-Scale Control on the Phytoplankton Biomass in Lake Victoria, Africa

Abstract: The relative bio-optical variability within Lake Victoria was analyzed through the spatio-temporal decomposition of a 1997–2004 dataset of remotely-sensed reflectance ratios in the visible spectral range. Results show a regular seasonal pattern with a phase shift (around 2 months) between the south and north parts of the lake. Interannual trends suggested a teleconnection between the lake dynamics and El-Niño phenomena. Both seasonal and interannual patterns were associated to conditions of light limitation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…The rise of the water temperature in Lake Victoria also resulted in higher stability of the water column (Hecky, 1993;Cózar et al, 2012) and may also have affected Nile perch distribution. For instance, Getabu et al (2003) observed high Nile perch densities in warmer, shallow waters.…”
Section: Introductionmentioning
confidence: 99%
“…The rise of the water temperature in Lake Victoria also resulted in higher stability of the water column (Hecky, 1993;Cózar et al, 2012) and may also have affected Nile perch distribution. For instance, Getabu et al (2003) observed high Nile perch densities in warmer, shallow waters.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the expected raise in climate fl uctua tions will occur with unprecedented levels by human impacts (Úbeda et al 2013). Typical examples are (1) eutrophication of rivers resulting in cyanobacteria blooms (Cózar et al 2012), (2) conversion of natural vegetation into pastures for cattle grazing, (3) conversion of Cerrado vegetation into crop fields in the high plateau headwaters, (4) environmental contamination (eg. agricultural chemicals and mercury contamination by gold mining), (5) unregulated tourism, (6) introduction of exotic species and (7) infrastructure and unplanned human occupation (Alho 2011, Nunes da Cunha and Junk 2015).…”
Section: Vegetation Faciesmentioning
confidence: 99%
“…Total nitrogen concentrations have increased since the 1960s, primarily through cyanobacteria fixation, and nitrogen generally follows a decreasing concentration pattern from the coast to offshore waters . While nutrient loading has created the light-limited conditions of the lake, seasonal and interannual variations in primary productivity are now driven primarily by climate (Silsbe et al 2006, Cózar et al 2012. This is of particular relevance since it highlights an important characteristic of qualitative models such as the one we use: they do not account for time or effect lags (Justus 2005).…”
Section: Box 3: Spatial Heterogeneity Of the Lakementioning
confidence: 99%
“…Indeed, the whole ecosystem is influenced by climate change , Cózar et al 2012) and has been degraded through eutrophication (Dobiesz et al 2010), which impoverishes the system by driving an irreversible decline in biodiversity (Seehausen et al 1997a). Beyond a certain threshold, eutrophication threatens to cause a more general collapse of stocks, not only of Nile perch (Kolding et al 2008).…”
Section: Introductionmentioning
confidence: 99%